Retinal Microvascular Changes in Mild Cognitive Impairment and Alzheimer's Disease: A Systematic Review, Meta-Analysis, and Meta-Regression - Yeh, Tsai-Chu; Kuo, Chun-Tung; Chou, Yu-Bai (Frontiers in Aging Neuroscience, 2022)
Background The remarkable increase in prevalence and significant morbidity of neurodegenerative diseases pose a tremendous burden for the health care system. Changes in retinal microvasculature metrics associated with Alzheimer's disease (AD) and mild cognitive impairment (MCI) may provide opportunities for early diagnosis and intervention. However, the role of retinal vascular biomarkers remains controversial. We aim to perform a systematic review, meta-analysis and meta-regression to evaluate the comprehensive retinal microvasculature changes in patients with AD and MCI. Methods We conducted a literature search on PubMed, MEDLINE, and EMBASE to identify studies published before May 2021 which assessed the measurements of optical coherence tomography angiography (OCTA) between AD, MCI with healthy control eyes, including foveal avascular zone (FAZ), vessel density (VD) of peripapillary, superficial and deep capillary plexus, and choroidal thickness using a random-effect model. We also performed meta-regression and subgroup analysis and assessed heterogeneity and publication bias to evaluate potential sources of bias. Results Compared with control eyes, VD of superficial capillary plexus was significantly lower in AD [standardized mean difference (SMD): −0.48; 95% CI (−0.70 to −0.27); p = 0.04] and MCI eyes [SMD: −0.42; 95% CI (−0.81 to −0.03); p = 0.03], as well as reduced VD of deep capillary plexus [SMD: −1.19; 95% CI (−2.00 to −0.38]; p < 0.001], [SMD: −0.53; 95% CI (−0.85 to −0.22); p < 0.001]. FAZ was significantly enlarged in AD eyes [SMD: 0.54; 95% CI (0.09 to 0.99); p = 0.02]. The meta-regression analysis showed that the OCTA machine type and macular scan size significantly influenced the variation of VD and FAZ between AD and control eyes (p < 0.05). Conclusion Our results highlight the potential of OCTA as a biomarker to detect early microvasculature deficits in AD and MCI. Notably, the macular scan size and different OCTA machine type could explain the heterogeneity observed in literatures. This information might be useful for future longitudinal study design to evaluate the role of OCTA in monitoring disease progression and treatment efficacy.